Boosting Speaking Skills through Native Speaker Practice at E-Fun Institute - Saputri, Avida Pramayshela; Sujito (Program Studi Pendidikan Bahasa Inggris, 2025)
This study explores the impact of practicing English speaking with native speakers on the speaking fluency and confidence of EFL students at E-Fun Institute, Central Java. Implementing a quantitative approach with a quasi-experimental design, the study involved 30 students from the intermediate speaking class, divided into an experimental group and a control group. Over four weeks, the experimental group participated in weekly 45-minute conversation sessions with native English speakers, while the control group engaged in peer-based speaking practice using conventional classroom methods. Pre-tests and post-tests were administered to measure students’ speaking fluency and self-confidence using standardized rubrics and Likert-scale questionnaires. Data were analyzed using SPSS 26, including descriptive statistics, paired samples t-tests, and independent samples t-tests. The findings showed a statistically significant improvement in both fluency and confidence among the experimental group compared to the control group. These results support the view that native speaker interaction provides valuable linguistic input, lowers learners’ affective filters, and enhances motivation. The study concludes that integrating native speaker-based speaking practice is an effective instructional strategy to improve oral communication skills in EFL contexts, especially within non-formal educational institutions.